Cumulative protective efficacy of rZot and rAce combination in challenge experiments with wild type Vibrio cholerae in mouse model. Issue 9 (2nd September 2018) - Anvari, Shaghayegh; Najar-Peerayeh, Shahin; Behmanesh, Mehrdad; Bakhshi, Bita
ABSTRACT: The aim of this study was to assess the cumulative immunogenicity properties of rZot and rAce combination and their potential ability to increase the clearance rate of pathogenic standard Vibrio cholerae strain in challenge experiments in mice model. The recombinant Zot and Ace proteins were produced and used to raise polyclonal antibodies of anti-Zot and anti-Ace recombinant proteins in rabbit. Six-week female BALB/c mice were immunized with different antigens via oral route. Blood samples were collected, and the total amount of IgG and IgA antibodies against rZot and rAce were measured in blood and stool samples of each immunized mouse. Challenge experiments were done with toxigenic V. cholerae strain. The anti-Zot and anti-Ace IgG titers were significantly higher in immunized mice in comparison with control group. The IgG and IgA titers were higher in the sera of mice immunized by recombinant Ace than in group immunized by rZot, indicating the higher immunogenicity of rAce than rZot. The use of rAce and rZot mixture led to synergistic activities in increasing the level of IgG and IgA in comparison with the use of each protein separately. The clearance rate was significantly higher in different challenge groups than in the control group, and the coherence between rZot and rAce reduced the bacterial shedding significantly. In conclusion, the use of recombinant Zot and Ace mixture can produce the proper amount of IgA and IgG against to toxigenic V. cholerae, reduce bacterial shedding in immunized mice significantly, and be used as a potent candidate in cholera vaccine research.